Uric Acid-HDL Ratio as Predictor of Major Cardiovascular Events in Very High Cardiovascular Risk Patients Treated with High-Intensity Statin Therapy - Mirza, Teuku; Heriansyah, Teuku; Zufry, Hendra; Mudatsir; Muqsith, Muhammad (South Eastern European Journal of Public Health, 2024)
Introduction: Uric acid levels are positively correlated with cardiovascular disease. High Density Lipoprotein (HDL) cholesterol plays a role in suppressing blood oxidation reactions and protecting vascular endothelial cells. The combination of these two metabolic parameters, the Uric Acid-HDL Ratio (UHR) makes it a very useful predictor marker for metabolic disorders. Statins are known to be the gold standard for raising HDL cholesterol. Some types of statins are also known to reduce serum uric acid levels by involving pleiotropic actions. The aim of this study was to determine baseline UHR as a predictor of MACE after administration of high-intensity statins. Objectives: The Objective of this study was to determine baseline UHR as a predictor of MACE after administration of high-intensity statins. Methods: This study was conducted at the cardiac center of Dr Zainal Abidin Regional General Hospital. This study is an observational study with a prospective cohort design. The target population was patients classified as patients with very high cardiovascular risk and using consecutive sampling techniques. Results: During the study period, a total of 82 patients with ischemic heart disease with very high cardiovascular risk met the inclusion and exclusion criteria. Of these, 49 patients (59.8%) were identified as having major cardiovascular events (MACE) while the remaining 33 patients (40.2%) did not had MACE. The results of this study are that statin therapy may not significantly affect the uric acid-HDL ratio in the context of major cardiovascular events. Conclusions: The uric acid-HDL ratio had no significant predictive ability for major cardiovascular events in patients with very high cardiovascular risk who were treated with high-intensity statin therapy.